Measuring human capital indicators and their role in future productivity in Syria during the period 2010-2022. - اسماعيل, روز (Submission and Review of Research -Biological Sciences Series, 2025)
The aim of the research was to measure and analyze the human capital index in Syria, with its components (survival, education, health) during the period 2010-2022, as it represents a critical stage in the history of Syria, as it witnessed major economic and social changes, which affected the indicators of human capital and productivity in the country. The research also aimed to measure the contribution of each component of human capital to future productivity The descriptive-analytical and quantitative approaches were adopted in studying the development of human resource investment indicators across the Syrian Arab Republic. The research community included the main groups involved in human resource investment, including educational institutions, government agencies, and private companies, ensuring the comprehensiveness and accuracy of the data in analyzing the development of the indicators The research results showed that the under-five mortality rate during the period studied was 29.6%, and the contribution to future productivity was 0.70, according to the survival index. The expected number of years of schooling was 8.91, according to the education quantity index.